A meta-analysis of FZD3 gene polymorphisms and their association with schizophrenia. (December 2016) - Pantavou, Katerina G.; Braliou, Georgia G.; Kontou, Panagiota I.; Dimou, Niki L.; Bagos, Pantelis G.
Abstract : Objective: The aim of this study was to investigate the potential association of FZD3 polymorphisms with schizophrenia. Methods: A systematic review and a meta-analysis were carried out comprising of nine genetic association studies, with both a population-based and a family-based design, and three genome-wide association studies. A total of 1601 family trios, 39 922 schizophrenic patients, and 61 287 healthy individuals were involved in the analysis and six polymorphisms were examined: rs2241802, rs2323019, rs352203, rs3757888, rs880481, and rs960914. A summary-based method for pooling genetic association studies under both family-based and population-based designs was used. Odds ratios along with their 95% confidence intervals were computed to compare the contrast of alleles in patients and controls. Results: The results indicate a potentially weaker effect of FZD3 polymorphisms on schizophrenia than that suggested originally and possibly limited to Chinese populations. No relationship was identified between all examined polymorphisms and schizophrenia, except for rs352203, which plays a protective role against schizophrenia. However, this effect was mainly attributed to studies including Chinese patients. In the Chinese population, evidence for an elevated risk for schizophrenia linked to the rs2323019 polymorphism was also identified. Conclusion: Given the different linkage disequilibrium patterns observed in Chinese populations, schizophrenia may be related to some other polymorphisms of gene FZD3 that are in stronger linkage disequilibrium to Chinese than to the other populations studied.